2011
DOI: 10.1016/j.bcp.2010.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific regulation of cytochrome P450 expression and activity by estradiol in female rats

Abstract: Estradiol (E2) is the major endogenous estrogen, and its plasma concentration increases up to 100-fold during pregnancy in humans. Accumulating evidence suggests that an elevated level of E2 may influence hepatic drug metabolism, potentially being responsible for altered drug metabolism during pregnancy. We characterized effects of E2 on expression and activities of cytochrome P450 enzymes (CYPs) in an in vivo system using rats. To this end, female rats were treated with estradiol benzoate (EB) or known CYP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…Elevated levels of hormones coupled with induction of ERa mRNA may be involved in the regulation of other nuclear receptors. A prior study demonstrated the downregulation of PXR and CAR in estradiol benzoate-treated rats (Choi et al, 2011). In addition, Cyp2b10 (CAR target gene) is induced by estradiol and repressed by progesterone in primary mouse hepatocytes, suggesting divergent regulation of this pathway by sex hormones (Kawamoto et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Elevated levels of hormones coupled with induction of ERa mRNA may be involved in the regulation of other nuclear receptors. A prior study demonstrated the downregulation of PXR and CAR in estradiol benzoate-treated rats (Choi et al, 2011). In addition, Cyp2b10 (CAR target gene) is induced by estradiol and repressed by progesterone in primary mouse hepatocytes, suggesting divergent regulation of this pathway by sex hormones (Kawamoto et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…For example, three studies in this issue of Drug Metabolism and Disposition approach the regulation of P450 enzymes by estrogens, progesterone, and their combination (Choi et al, 2013;Dickmann and Isoherranen, 2013;Papageorgiou et al, 2013). Together with past evaluations of regulation of P450 enzymes by estrogens (Choi and Jeong, 2009;Mwinyi et al, 2010;Choi et al, 2011;Koh et al, 2012), these studies clearly show that pregnancyrelated hormones regulate P450 mRNA in vitro. However, as highlighted in the articles, during pregnancy maternal hepatocytes are exposed to a combination of hormones and growth factors that may act in a synergistic or antagonistic manner, and dissecting individual mechanisms and regulators will require more in vivo studies during pregnancy as well as more detailed in vitro studies.…”
Section: Mechanistic Studies Using In Vitro Systems To Evaluate Regulmentioning
confidence: 87%
“…Hepatocytes were treated with vehicle control (ethanol), a female hormone, or one of the known inducers for 72 hours, and P450 activities were determined as previously described elsewhere Choi et al, 2011). Briefly, the media were replaced with fresh media containing one of P450 isoform-selective probe substrates for CYP1A2 (50 mM phenacetin), CYP2A6 (100 mM coumarin), CYP2B6 dmd.aspetjournals.org (100 mM S-mephenytoin), CYP2C9 (100 mM diclofenac), CYP2C19 (100 mM S-mephenytoin), CYP2D6 (60 mM bufuralol), CYP2E1 (100 mM p-nitrophenol), and CYP3A4 (15 mM midazolam) and sampled at various time points (30 minutes to 4 hours).…”
Section: Methodsmentioning
confidence: 99%
“…Separation was performed with a Zorbax Eclipse XDB-C8 column (4.6 Â 50 mm, 3.5 mm) (Agilent Technologies, Santa Clara, CA) except for acetaminophen and 7-hydroxycoumarin (YMC C8 4.6 Â 150 mm, 3.5 mm, Waters, Milford, MA). The quantitative analytical conditions for the metabolites (e.g., internal standards, MRM pairs, and mobile phase gradients) have been previously described Choi et al, 2011).…”
Section: Methodsmentioning
confidence: 99%